2020
DOI: 10.18805/ijar.b-1192
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin Sub-Inhibitory Concentration Affects Streptococcus suis Biofilm Formation and Virulence Gene Expression

Abstract: Streptococcus suis (S. suis) is a major pathogen causing economic losses to the swine industry. Norfloxacins are usually used at sub-MIC (Minimum Inhibitory Concentration) doses to prevent S. suis infection. This study demonstrates the effect of norfloxacin sub-MIC on biofilm formation and virulence gene expression in S. suis.It was found that 1/4 MIC of norfloxacin increased biofilm formation in S. suis, the biofilms formed contained a higher number of viable bacteria. Additionally, bacterial growth rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Additionally, studies have shown that a sub-inhibitory concentration of antibiotics may affect the virulence genes of bacteria, such as Panton-Valentine-leucocidin (PVL), alpha-hemolysin (Hla), and phenol-soluble-modulin alpha (PSMα) [ 16 , 17 ]. The previous experiments of our research group confirmed this view [ 18 ]. Norfloxacin can significantly down-regulate the key virulence genes of S. suis , such as capsular polysaccharide (CPS), extracellular factor (EF), hemolysin (SLY), fibronectin and fibrinogen binding protein (FBPS), glutamate dehydrogenase (GDH), and glycerophosphate deoxygenase (GAPDH).…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, studies have shown that a sub-inhibitory concentration of antibiotics may affect the virulence genes of bacteria, such as Panton-Valentine-leucocidin (PVL), alpha-hemolysin (Hla), and phenol-soluble-modulin alpha (PSMα) [ 16 , 17 ]. The previous experiments of our research group confirmed this view [ 18 ]. Norfloxacin can significantly down-regulate the key virulence genes of S. suis , such as capsular polysaccharide (CPS), extracellular factor (EF), hemolysin (SLY), fibronectin and fibrinogen binding protein (FBPS), glutamate dehydrogenase (GDH), and glycerophosphate deoxygenase (GAPDH).…”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, the results of tissue HE staining ( Figure 5 ) showed that, after treatment with 1/4MIC Amoxicillin and Tylosin, respectively, the damage degree of each tissue was significantly lower than that of the control group, which indicates that 1/4MIC Amoxicillin and Tylosin might be involved in the expression of multiple genes that regulate bacterial virulence [ 36 ]. We selected seven virulence-related genes in S. suis for verification, which were ef , fbps , gapdh , gdh , mrp , and sly [ 18 ]. Compared with the control group, 1/4MIC Amoxicillin and Tylosin can significantly down-regulate the gene expression of ef , fbps , gapdh , gdh , mrp , and sly .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that bacteria growing in a biofilm are intrinsically resistant to many antibiotics (Li et al, 2020). The improvement of bacterial resistance can cause the disease to prolong and the formation of biofilm is one of the important reasons for the improvement of drug resistance (Wang et al, 2019).…”
Section: Comparison Of Antibiotic Resistance Rates Between Planktonicmentioning
confidence: 99%
“…Melting curve analysis was performed at 95C for 10 sec and 65C for 5 sec. Results are expressed as the fold changes calculated using the comparative 2 -ΔΔCt method (Liu et al, 2020). Liver tissues (50 mg) were lysed using protein extraction solution (iNtronbio, Korea) and quantified using a bicinchoninic acid assay kit (Pierce, USA).…”
Section: Introductionmentioning
confidence: 99%